2013
DOI: 10.1209/0295-5075/104/27012
|View full text |Cite
|
Sign up to set email alerts
|

Phase stability, magnetism and generalized electron-filling rule of vanadium-based inverse Heusler compounds

Abstract: By using first-principles calculations, we have systematically investigated the phase stability, magnetism and electron-filling behavior of vanadium-based inverse Heusler compounds. Our calculation results indicate that, due to the complex hybridization of the d orbitals for the vanadium atom, the electronic structures of the vanadium-based inverse Heusler compounds show two opened gaps (one locates in the spin-up channel and the other in the spin-down channel) near the Fermi level, originating from different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Damewood et al found that these LiMnZ (Z = N, P, Si) alloys show HM behaviors with large semiconducting-type band-gaps and magnetic moments (>3 μ B per formula unit) at their strained lattice constants. To our best knowledge, based on the the Slater-Pauling (S-P) and generalized electron-filling rules [ 17 , 18 , 19 , 20 ], the largest magnetic moment of the half-Heusler-type alloy should be 5 μ B per formula unit. Due to the large semiconducting-type band-gaps and the large magnetic moments, LiMnZ (Z = N, P, Si) alloys may be good candidates for spintronic materials for devices operating at or above room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Damewood et al found that these LiMnZ (Z = N, P, Si) alloys show HM behaviors with large semiconducting-type band-gaps and magnetic moments (>3 μ B per formula unit) at their strained lattice constants. To our best knowledge, based on the the Slater-Pauling (S-P) and generalized electron-filling rules [ 17 , 18 , 19 , 20 ], the largest magnetic moment of the half-Heusler-type alloy should be 5 μ B per formula unit. Due to the large semiconducting-type band-gaps and the large magnetic moments, LiMnZ (Z = N, P, Si) alloys may be good candidates for spintronic materials for devices operating at or above room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, from the obtained total DOS, we calculated the spin polarization ( p ) at Fermi energy of XA and L2 1 types Hf 2 VZ. The spin polarization p (%) that can be defined as the ratio of the difference to sum of the DOS values of spin up and spin down version at the Fermi-level [ 13 , 16 ], represented by mathematical formulation as a percent; where the n ↑ ( E f ) and n ↓ ( E f ) stand for the spin-dependent DOS around the Fermi level. The results have been given in Table 3 , we can see that the p of XA-type Hf 2 VZ are quite high (>88%), even some alloys (such as Hf 2 VAl) have completely spin polarization (100%).…”
Section: Resultsmentioning
confidence: 99%
“…Heusler alloys are a noticeable class of intermetallic materials that represent as usual by the formula X 2 YZ (often called full-Heusler) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ] or XYZ (usually named as half-Heusler) [ 16 ], where X, Y are transition-metal-element atoms and Z is a main group element. The structure of full-Heusler alloys consists of four interpenetrating fcc lattices with four equidistant sites as basis along the diagonal of the unit cell.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, an e u -t 1u band gap is created in the spin-up channel. Based on the generalized electron-filling rule (Zhang, Xu et al, 2013;, for MCoVZ the total numbers of occupied states are 12 and 9 in the spin-up and spin-down channels, respectively, and therefore there is a total spin magnetic moment of 3 m B .…”
Section: Tablementioning
confidence: 99%